2020
DOI: 10.1111/jopr.13216
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Accuracy of Image Registration Methods for Merging Optical Scan and Radiographic Data in Edentulous Jaws

Abstract: Purpose: The image registration of optical scans to radiographic images is essential for performing computer-guided implant surgery. This study aimed to evaluate the effect of different image matching conditions on the accuracy of image registration for computer-guided implant surgery in completely edentulous jaws. Materials and Methods: The optical scan image of a completely edentulous study model was registered to the respective cone-beam computed tomography data using three different image matching conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A prerequisite for a 3D comparative study was the reliable registration method of 3D models (also named alignment, registration, superimposed, or overlapped) [3,4,5,9,10]. Registration is also an indispensable tool for digital clinical dentistry of edentulous jaws [11,12], such as transferring jaw relations in digital complete dentures, aligning jaw relation records with impressions, and aligning radiographic templates with CBCT in preoperative implant design [13,14,15,16]. There are three main recorded model registration methods in the literature: Scanner's own software, such as 3Shape, which performs alignment by manually selecting three points and calculating internally [5]; Reverse engineering software, in which the most widely used registration method is the best t alignment tool [ 2,3,6,7], which is also recommended for model alignment in reverse engineering software for product quality analysis; and When Chen Sihan et al studied the accuracy of intraoral scanning of complete dentition, they used the manual registration command rst and then the global registration command for model alignment in reverse engineering software [8].…”
Section: Discussionmentioning
confidence: 99%
“…A prerequisite for a 3D comparative study was the reliable registration method of 3D models (also named alignment, registration, superimposed, or overlapped) [3,4,5,9,10]. Registration is also an indispensable tool for digital clinical dentistry of edentulous jaws [11,12], such as transferring jaw relations in digital complete dentures, aligning jaw relation records with impressions, and aligning radiographic templates with CBCT in preoperative implant design [13,14,15,16]. There are three main recorded model registration methods in the literature: Scanner's own software, such as 3Shape, which performs alignment by manually selecting three points and calculating internally [5]; Reverse engineering software, in which the most widely used registration method is the best t alignment tool [ 2,3,6,7], which is also recommended for model alignment in reverse engineering software for product quality analysis; and When Chen Sihan et al studied the accuracy of intraoral scanning of complete dentition, they used the manual registration command rst and then the global registration command for model alignment in reverse engineering software [8].…”
Section: Discussionmentioning
confidence: 99%
“…It is found that the measured values of CBCT are significantly lower than those of the model scanner and IOS ( P < 0.001). Other scholars [ 27 ] studied the influence of registration conditions of optical scanning images and radiation images on the accuracy and found that the accuracy based on full-surface registration is higher than that based on the local matching. In the study of the implant systems and guide design software, Ashtiani et al [ 28 ] reviewed the deviations of 6 kinds of guide design software, among which 3Shape shows smaller mean angle deviation, coronal deviation, and apical deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Critically, the original image quality of CBCT could profoundly affect the result of the best-fit algorithm process. Indistinctive radiographic images can lead to a poor result of the registration [22]. Flügge et al used CBCT data and intraoral surface scans of 36 patients to examine the influence of the operator, the preprocessing of data, and image artifacts on registration accuracy [19].…”
Section: Discussionmentioning
confidence: 99%